2011
DOI: 10.1007/s00586-011-1724-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of double-door laminoplasty using hydroxyapatite spacers in patients with compressive cervical myelopathy

Abstract: No previous studies have reported 10-year follow-up results for double-door laminoplasty using hydroxyapatite (HA) spacers. The purpose of this study was therefore to explore the long-term results of doubledoor laminoplasty using HA spacers and to determine if non-union or breakage of HA spacers is related to restenosis of the enlarged cervical canal. The study group consisted of 68 patients with a minimum of 10 years of follow-up after double-door laminoplasty using HA spacers. The average postoperative Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…Furthermore, although preservation of the terminal ligaments may confer biomechanical stability, this cadaveric study cannot address long-term sequelae of more stabilized cervical vertebrae, especially at C2-3, which can become ossified after laminoplasty, 23 possibly conveying recalcitrant stenosis at this level. 11 This, of course, would require long-term clinical data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although preservation of the terminal ligaments may confer biomechanical stability, this cadaveric study cannot address long-term sequelae of more stabilized cervical vertebrae, especially at C2-3, which can become ossified after laminoplasty, 23 possibly conveying recalcitrant stenosis at this level. 11 This, of course, would require long-term clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,16,28 Despite these advantages, reports have shown that ODL may lead to persistent neck and shoulder pain, progressive loss of ROM, and progressive cervical kyphosis. [6][7][8]11,29 There are various approaches used to perform cervical laminoplasty, many of which involve spinous process resection and disruption of intervening interspinales musculature and supraspinous ligaments (intraspinous and supraspinous ligaments [ISLs]). 5,9,20 Alternative methods have been reported that retain the dorsal ligamentous complex, and small cohorts have shown it may protect from loss of sagittal balance, while not statistically reducing cervical ROM.…”
mentioning
confidence: 99%
“…This technique is well established and the reported complication rates are acceptable, but some problems such as axial symptoms or C5 palsy have not been fully resolved [4][5][6]. The long term results of this technique is satisfactory, with the preservation of the enlarged cervical canal area and the maintenance of JOA scores for cervical myelopathy (JOA score, Table 1, maximum score 17 points) [7].…”
Section: Introductionmentioning
confidence: 98%
“…This method has become the gold standard for cervical myelopathy surgical interventions, particularly when there is multilevel involvement. Good long term surgical outcomes have been reported with this procedure [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 89%